THE NARCISSIST PERSONALITY TYPE AND RELATIONSHIPS: ANALYSIS FROM MALE AND FEMALE PERSPECTIVES - Alquliyev, Vüsal (Revista Gênero e Interdisciplinaridade, 2024)
This article analyzes the dynamics of narcissistic personality disorder in male and female relationships. Narcissistic individuals are characterized by high self-esteem, lack of empathy, and manipulative behavior. The fact that such persons put their needs in the center in their relationships and are prone to emotional manipulation towards their partners has a negative impact on the strength of relationships and the emotional sphere. The article also highlights the differences between narcissistic men and women and explores the problems gender-specific behavior patterns create in relationships. The results show that people who are in relationships with individuals with narcissistic personality traits can suffer serious psychological damage, and in such cases, the need for professional intervention comes to the fore. This study provides an in-depth understanding of the difficulties narcissistic personality poses in romantic relationships and has important implications for contemporary psychological research.